Innovative Financing Strategies in the Small and Medium Business Sector, Tapping the Right Sources - Chikwira, Collin; Rawjee, Veena Parbloo (The Journal of Accounting and Management, 2022)
Small and medium businesses are remaining small due to financial incapacitation. Literally financial resources are the limiting factors for growth; therefore, the study explore what could be the most optimal sources of financing models for sustainability in the small and medium fraternity after Covid 19 pandemic. The research adopted mixed methodology. The data was collected using structured questionnaires on a face to face, telephonic, emails, and virtual methods. The survey was more concerned with both quantitative and qualitative sources of finance on both preferred and the business is using. The results show that the financing preferences of owner/managers all the selected Districts changed according to the development needs of their SMEs. At the start-up stage, most owner/managers appear to have relied considerably upon their own savings as well as the financial support of their immediate family. After two years of economic viability, the SMEs in the sample seem to have increased their reliance upon the support of financial institutions. The findings had a positive social-economic impact if small businesses sustain for a near future and which it means that there will generate employment, income and improve welfare in the communities of operations